2020
DOI: 10.1016/j.jot.2019.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of a novel robotic system for pedicle screw fixation: A randomised controlled trial

Abstract: Background and objectiveExisting orthopaedic robotic systems are almost restricted to provide guidance for trajectory direction. In the present study, a novel spinal robotic system with automatic drilling power was introduced. The aim of this study is to evaluate the feasibility and safety in pedicle screw ​insertion of posterior lumbar interbody fusion assisted by this novel robotic system.Methods and materialsA randomised controlled trial was conducted for 17 participants who were required posterior lumbar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 32 publications
(35 reference statements)
0
33
0
Order By: Relevance
“…Most spinal surgery robots are shared-control robots that simultaneously provide both the surgeon and robot the ability to control instruments and motions [25]. There are several studies evaluating the utility of pedicle-screw implantation using robotic-guided spine surgery with different systems, such as, Mazor X, Mazor Robotics Ltd., Caesarea, Israel [26], Mazor [27], SpineAssist Mazor [9,12,[28][29][30], Excelsius GPS ® ; Globus Medical, Inc. Audubon, PA, USA [2,31,32], ROSA spine robot technology (Zimmer-Biomet, Warsaw, Indiana, USA) [33], Orthbot [34] and TiRobot [35]. Unfortunately, direct comparisons of screw placement accuracy between these systems are difficult because of the significant cost and time associated with their adoption [36].…”
Section: Previous Studies On Use Of Other System For Robotic-guided Spine Surgerymentioning
confidence: 99%
“…Most spinal surgery robots are shared-control robots that simultaneously provide both the surgeon and robot the ability to control instruments and motions [25]. There are several studies evaluating the utility of pedicle-screw implantation using robotic-guided spine surgery with different systems, such as, Mazor X, Mazor Robotics Ltd., Caesarea, Israel [26], Mazor [27], SpineAssist Mazor [9,12,[28][29][30], Excelsius GPS ® ; Globus Medical, Inc. Audubon, PA, USA [2,31,32], ROSA spine robot technology (Zimmer-Biomet, Warsaw, Indiana, USA) [33], Orthbot [34] and TiRobot [35]. Unfortunately, direct comparisons of screw placement accuracy between these systems are difficult because of the significant cost and time associated with their adoption [36].…”
Section: Previous Studies On Use Of Other System For Robotic-guided Spine Surgerymentioning
confidence: 99%
“…The flow diagram in Figure 1 shows the patient selection process, with inclusion and exclusion criteria. 2046 participants (male: 46.22%; female: 53.78%) were included from 26 trials, 3 , 5 , 11 , 12 , 13 , 14 , 16 , 17 , 18 , 19 , 21 , 22 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 conducted in China ( n = 9), 3 , 11 , 16 , 19 , 36 , 38 , 39 , 40 , 41 Germany ( n = 7), 12 , 17 , 18 , 22 , 30 , 32 , 37 the United States of America ( n = 3), 28 , 31 , 33 Switzerland ( n = 3), 5 , 29 , 35 South Korea ( n = 3) 13 , 21 , 34 and France ( n = 1). 14 The robotic systems used for pedicle screw placement included SpineAssist ( n = 10), 5 , 12 , 18 , 22 , 28 …”
Section: Resultsmentioning
confidence: 99%
“… 14 The robotic systems used for pedicle screw placement included SpineAssist ( n = 10), 5 , 12 , 18 , 22 , 28 , 29 , 30 , 32 , 35 Renaissance ( n = 7), 3 , 13 , 17 , 21 , 33 , 34 , 37 TiR7obot ( n = 7), 16 , 19 , 36 , 38 , 39 , 40 , 41 ROSA ( n = 1), 14 and Orthbot ( n = 1). 11 Five studies were found to have a low risk for randomization sequence generation 13 , 16 , 21 , 34 , 36 and four did not provide this information. 11 , 22 , 30 , 39 Seven studies showed a low risk in concealing allocation, 11 , 13 , 16 , 21 , 34 , 36 , 39 with two not providing this information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations